2017
DOI: 10.5606/ehc.2017.54608
|View full text |Cite
|
Sign up to set email alerts
|

Carpometacarpal fracture dislocation of the fourth and fifth finger: mid-term results of 15 patients

Abstract: ÖZAmaç: Bu çalışmada karpometakarpal (KMK) kırıklı çıkık nedeniyle açık veya kapalı redüksiyon ile tedavi edilen hastaların orta dönem klinik takip sonuçları geriye dönük olarak değerlendirilip karşılaştırıldı. Hastalar ve yöntemler: Dördüncü ve beşinci parmak KMK kırıklı çıkık nedeniyle ameliyat edilen 15 hastanın (1 erkek, 14 kadın; ort. yaş 32.5±10.5 yıl; dağılım 18-55 yıl) tıbbi çizelgeleri incelendi. Hastalar uygulanan tedaviye göre kapalı redüksiyon ve perkütan pinleme (KRPP, n= 6) ve açık redüksiyon ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…11 Even though no treatment modality has proven to be superior in randomized controlled trials, studies by Bao et al and Gülabi et al found that patients managed by CRPP had better DASH scores and grip strength than those treated with ORIF. 12,13 Surgery should be ideally performed during the first 7 to 10 days after injury 5 ; however, we performed successfully 1 case even at the 20th day. Physiotherapy of hand and wrist joint is required after 6 weeks of wrist immobilization in safety position to avoid postoperative stiffness.…”
Section: Discussionmentioning
confidence: 89%
“…11 Even though no treatment modality has proven to be superior in randomized controlled trials, studies by Bao et al and Gülabi et al found that patients managed by CRPP had better DASH scores and grip strength than those treated with ORIF. 12,13 Surgery should be ideally performed during the first 7 to 10 days after injury 5 ; however, we performed successfully 1 case even at the 20th day. Physiotherapy of hand and wrist joint is required after 6 weeks of wrist immobilization in safety position to avoid postoperative stiffness.…”
Section: Discussionmentioning
confidence: 89%
“…Less than 1% of the injuries affecting the hand and wrist are multiple fracture dislocations of the CMC joint. [4] Because of the strong ligamentous attachments to the carpal bones, multiple fracture dislocation of the CMC joint usually occurs together with avulsion and impaction fractures. [5] Dorsal dislocations are more common than volar dislocations.…”
mentioning
confidence: 99%
“…[6] Direct traumas forcing metacarpals to hyperflexion cause CMC joint dislocation. [4,6] In the presence of severe swelling, pain, deformity, ecchymosis, and abrasion of the hand, multiple CMC fracture dislocations should be suspected. Severe swelling can cause compartment syndrome.…”
mentioning
confidence: 99%